Frequency Spectrum Analysis of Partial Discharge Measurement in 150-kV Outdoor Cable Sealing End—A Case Study - Muhammad Kodrat; Umar Khayam (IEEE Access)
Partial Discharge (PD) is part of the initiation of failure in the insulation part of cable sealing end (CSE) equipment. CSE with a complex manufacturing form, the interface between insulating materials is part of the challenge to detect PD accurately. In this paper, we design and deploy a new UHF antenna sensor design to detect PD signals in power equipment including CSE with its challenges. In addition, information is provided on the range of frequency spectrum present in CSE using frequency domain analysis. The proposed UHF sensor is designed with a size of 100mm x 80mm x 1.6mm in the form of a circular patch with an arm. This new UHF sensor is optimized and fabricated to produce a bandwidth of 0 - 3800 MHz and a voltage standing wave ratio (VSWR) of 1.1. To comply with the level of range of frequencies occurring and the level of sensitivity of the proposed sensor, an online measurement application is carried out on 6 units of 150 kV outdoor CSE. Measurement results from the implementation of the new UHF sensor design are able to detect PD signals in CSE. The frequency spectrum range of PD signals detected from distributed between 400 MHz to 1 GHz. The newly designed UHF sensor confirmed that it can be part of a measurement instrument to be applied to PD monitoring systems in high voltage/medium voltage power apparatus.